STUDI KUALITATIF PERSEPSI DAN PENGALAMAN HIDUP DENGAN DIDIAGNOSIS DIABETES MELITUS - MUNTAMAH, UMMU; Purwaningsih, Puji; Susanto, Hardhono; Ediati, Annastasia; Dwiantoro, Luky (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Backgraund: Diabetes Mellitus and Diabetes Distress are global problems that were interconnected. Someone who was diagnosed with DM, will be placed in a stress condition because the patient feels difficult with the many demands for self-care with DM. Objective: This study aims to explore the experience and understanding of diabetes, feelings after being diagnosed with diabetes, efforts made when facing difficulties. Methods: This research is a qualitative study. We used semi-structured interviews. This report was written following COREQ guidelines. Thematic analysis was applied to analyze the data. Results: there were four themes; 1) understanding the right DM is important to provide adequate understanding so that diabetes self-care activities can be carried out correctly, 2) attitude and behavior as well as inaccurate information can trigger situations that are threatening to cause severe diabetes, 3) the right efforts to deal with threatening situations can prevent the occurrence of severe diabetes, and 4) the role and support of others to help solve problems effectively as expected. Conclution: The perception and experience of patients living with diabetes mellitus is to assume that DM is a diabetes disease that is difficult to cure. The perceived response is shock, sadness, bore, stress, and fear